Nine new species of the genus Deinopteroloma Jansson, 1946 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini) from China and Vietnam - Shavrin, Alexey V.; Smetana, Aleš (Zootaxa, 2016)
Nine new species of the genus Deinopteroloma Jansson, 1946 are described and illustrated: D. bisbisinuatum sp.n. and D. draco sp.n. from China, Sichuan (Gongga Shan), D. emeicola sp.n., D. minor sp.n., D. ruzickai sp.n., D. sextuberculatum sp.n. and D. yinyang sp.n. from China, Sichuan (Emei Shan), D. rougemonti sp.n. from China, Yunnan (Dehong Dai and Jingpo Autonomous Prefecture) and D. vesiculosum sp.n. from North Vietnam. Three species groups within the genus are identified and characterized and closely relationships among them are briefly discussed. A check-list and key to the species of Deinopteroloma are provided. The distribution of all described and recorded species is mapped. Additional records of D. spectabile Smetana, 1996 from Nepal are given.